Ergonomic Redesign of the Coca Cola Freestyle Machine Graphical User Interface to Improve Accessibility - Hannan, Rebecca; Laform, Samantha; Boyle, Kate; Danziger, Samuel; Mahyoub, Mohammed A.; Gao Smith, Tianqi (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 2020)
The purpose of this research is to redesign the graphical user interface of the Coca Cola Freestyle machine to improve its usability for individuals with visual impairments. The proposed design included a feature to increase text and button size. Also, the drink selection process was reordered. In this study, the original display and the redesign were implemented on a touchscreen laptop to emulate the actual process. Ten subjects with normal and impaired vision were recruited respectively and were randomly assigned to complete a drink selection task in using either the “Original” GUI or a “Redesign” created by the authors (n=5).User feedback was collected and analyzed. The drink dispensing task completion time was recorded and analyzed using two-way ANOVA and Tukey pairwise comparison. It was concluded that the original design was easier to navigate in terms of icon position, but the redesign was preferred because of its flexibility to change the text size.